Relative Effectiveness and Safety of the GLP-1 (Glucagon-Like Peptide 1) Receptor Agonists, Semaglutide and Liraglutide in the Treatment of Obese Type 2 Diabetics: A Prospective Observational Cohort Study in Poland - Hoffmann K; Michalak M; Paczkowska A (Diabetes, Metabolic Syndrome and Obesity)
Karolina Hoffmann,1 Michał Michalak,2 Anna Paczkowska3 1Department and Clinic of Internal Diseases and Metabolic Disorders, Poznan University of Medical Sciences, Poznań, Poland; 2Department of Computer Science and Statistics, Poznan University of Medical Sciences, Poznań, Poland; 3Department of Pharmacoeconomics and Social Pharmacy, Poznan University of Medical Sciences, Poznań, PolandCorrespondence: Karolina Hoffmann, Department and Clinic of Internal Diseases and Metabolic Disorders, Poznan University of Medical Sciences, Przybyszewskiego 49 Street, 60-355, Poznań, Poland, Tel +4861 8549 377, Fax +4861 8478 529, Email karolinahoffmann@ump.edu.plPurpose: To compare the efficacy and safety of semaglutide and liraglutide over one year in obese Polish patients with type 2 diabetes.Patients and Methods: In this prospective, observational cohort study conducted in Poland in 2024, 460 patients aged 18– 80 were enrolled: 333 received semaglutide (Group 1), and 133 received liraglutide (Group 2).Results: After 12 months, HbA1c levels significantly decreased in both groups: Group 1: from 6.09 ± 1.14% to 5.42 ± 0.82% (mean decrease: 0.67 ± 0.37%, p< 0.0001). Group 2: from 5.78 ± 0.75% to 5.17 ± 0.54% (mean decrease: 0.61 ± 0.28%, p< 0.001). BMI decreased by 5.36 ± 3.45 kg/m² in Group 1 and 4.41 ± 4.63 kg/m² in Group 2 (p< 0.0001), with greater reduction in Group 1 (p=0.017). Gastrointestinal adverse effects were most common, including nausea, vomiting, constipation, gastritis, and diarrhea, with higher incidence in Group 1. HbA1c reduction correlated with baseline HbA1c, age, and gender; BMI reduction correlated with baseline HbA1c and BMI.Conclusion: Semaglutide was more effective than liraglutide in reducing HbA1c and BMI. Gastrointestinal symptoms were the most frequent side effects in both groups.Keywords: GLP-1 receptor agonist, semaglutide, liraglutide, obesity, type 2 diabetes